Factors associated with good death as perceived by terminally-ill patients, family members, and health care providers at the Cancer Institute and Supportive Palliative and Hospice Care Clinic, UP-PGH - Balein, Gemma N. (2008)
Several studies abroad have already explored the factors considered important at end of life among terminally-ill patients, family members and healthcare providers. Results gathered ranged from "freedom from pain", "autonomy, control and independence", "acceptance, closure most often at home", to "medicare care, sensitivity to religious and spiritual values, living well with God." This study focuses on factors associated with good death as perceived by terminally-ill patients, family members and healthcare providers. Specifically, it aims to know what factors at end of life wii be rated as extremely important by more than 70% of the survey participants and to find out which factors will be selected and ranked as five most important at end of life. Structured face to face interviews, using a modified 35-item questionnaire, were conducted among 35 patients, 41 family members and 34 healthcare providers at the Supportive Palliative and Hospice Care Clinic and the Cancer Institute, University of the Philippines-Philippine General Hospital. Descriptive statistics and weighted mean were used to determine the perceptions regarding factors associated with good death. One-way ANOVA and Multiple Comparisons scheffe tests, were used to examine the significance of specific response differences among groups. A major finding of this study is the strong agreement among end-of-life care participants' definitions of what constitutes a good death. One of the survey items showed consensus among all 3 groups. Survey participants overwhelmingly ranked "Come to peace with God" as the 1st most important. Regardless of role, respondents converged on the importance of spiritual support at the end of life. The findings of this study were used as a spring board to augment the understanding of good death. A crucial part of the discussion is the revisiting of the literature review in light of the research findings and concludes with implications and potential impacts this research project has in the fields of medicine, bioethics and society at large.
"March 2008."
Thesis (M.S. Bioethics)--University of the Philippines Diliman.
Keywords: Death -- Religious aspects -- Christianity; Death -- Philippines -- Psychological aspects; Death -- Moral and ethical aspects -- Philippines; Death -- Social aspects -- Philippines; Hospice care -- Philippines -- Manila; Terminal care -- Philippines